Heptaphylline induces apoptosis in human colon adenocarcinoma cells through Bid and Akt/NF-κB (p65) pathways - Chantana Boonyarat (2018)
Heptaphylline derivatives are carbazoles in Clausena harmandiana, a medicinal plant that is utilized for headache, stomach ache, and other treatments of illness. The present study examined the effects of heptaphylline and 7-methoxyheptaphylline on apoptosis of human colon adenocarcinoma cells (HT-29 cell line). Quantification of cell viability was performed using cell proliferation assay (MTT assay) and of protein expression through immunoblotting. The results showed that only heptaphylline, but not 7-methoxyheptaphylline, significantly significantly activated cleaved of caspase-3 and poly (ADP-ribose) polymerase (PARP-1) which resulted in HT-29 cell death. We found that heptaphylline activated BH3 interacting-domain death agonist (Bid) and Bak, proapoptotic proteins. In contrast, it suppressed X-linked inhibitor-of-apoptosis protein (XIAP), Bcl-xL and survivin, inhibitors of apoptosis. In addition, heptaphylline inhibited activation of NF-κB/p65 (rel), a regulator of apoptotic regulating proteins by suppressing the activation of Akt and IKKα, upstream regulators of p65. The findings suggested that heptaphylline induces apoptosis in human colon adenocarcinoma cells .